2020
DOI: 10.1073/pnas.2005242117
|View full text |Cite
|
Sign up to set email alerts
|

Complex mortuary dynamics in the Upper Paleolithic of the decorated Grotte de Cussac, France

Abstract: The Mid-Upper Paleolithic (Gravettian) karstic Grotte de Cussac (France) contains two areas of human remains in the context of abundant (and spectacular) parietal engravings. The first area (loci 1 and 2) includes the skeleton of a young adult male in a bear nest, rearranged by postdecomposition inundation, and the variably fragmentary remains of at least two individuals distributed across two bear nests, sorted anatomically and with most of the elements constrained to one side of one nest. The second … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Several sites in SWF also delivered female figures carved on cave-wall (Cussac) or fallen rocks (Laussel) or made of ivory (Brassempouy, Lespugue) or soft stones (Tursac, Sireuil), that are often stylistically compared to the ones known in the rest of Europe (see for instance 30 , 31 ). Gravettian in SWF is also characterized by complex funerary behaviours implying deliberate commingling of the remains of several individuals, unique in the MUP mortuary landscape 32 – 34 . To date, no nuclear DNA has been extracted from SWF MUP human remains, but a mitochondrial DNA (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Several sites in SWF also delivered female figures carved on cave-wall (Cussac) or fallen rocks (Laussel) or made of ivory (Brassempouy, Lespugue) or soft stones (Tursac, Sireuil), that are often stylistically compared to the ones known in the rest of Europe (see for instance 30 , 31 ). Gravettian in SWF is also characterized by complex funerary behaviours implying deliberate commingling of the remains of several individuals, unique in the MUP mortuary landscape 32 – 34 . To date, no nuclear DNA has been extracted from SWF MUP human remains, but a mitochondrial DNA (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…All the evidence suggests a minimal number of incursions, maybe one generation of human groups. Meanwhile, we cannot affirm that the bodies deposited in the bear nests and the individuals who deposited them belonged to the same group 44 although this is the most parsimonious hypothesis in the current state of analysis. Nevertheless, the study of foot bones found in the cave will also shed new light on the question of footwear.…”
Section: Discussionmentioning
confidence: 68%
“…Cro‐Magnon and Abri Pataud, among others), funerary traditions possibly included the alteration of burials, displacements and mixing of human remains (Kacki et al . 2020). Both study of allochthonous lithic raw material origin (as far as 240 km northeast in the Iberian Middle Gravettian) and similarities in personal ornament (such as pierced deer femoral heads) and burial practices between Aquitanian and Catalan regions suggest the permanence of long‐distance trans‐Pyrenean contact during the Final Gravettian (Marreiros et al .…”
Section: Discussionmentioning
confidence: 99%